(untitled) (Research, Society and Development, 2022)
Over the years, the label and packaging have gained greater popularity among the population, and today they are the biggest channel of communication between the brand and the consumer at the moment of making a purchase decision. The labeling of food products is a matter of concern among industries and consumers. Society’s demand for reliable and easy-to-understand information is increasing. The label has much information inscribed so that the consumer can make his purchase decision based on them but, it is not acknowledged if the majority population understands what is written. The present work sought to verify if consumers read the labels and understand the numerous information presented, whether described or utilized symbologies. The study was carried out via an online questionnaire prepared on the Google Forms platform, and disseminated by means of online social networks (Instagram, Facebook, WhatsApp) and e-mail. Five hundred (500) over 18 years old people from the Southeast region of Brazil with different educational levels, family social class, and marital status were interviewed. It appears that 52% of consumers understand the images and instructions contained on the labels in general and that the educational level interferes with the respondents’ understanding.